Men's participation in early childhood education and care (ECEC): comparative perspectives from Edinburgh, Scotland and Tianjin, China. Issue 3 (3rd July 2022) - Xu, Yuwei; Schweisfurth, Michele; Read, Barbara
ABSTRACT: At the global level, prominent narratives about improving the quality of early childhood education and care (ECEC) promote the recruitment of men into the profession. However, comparing across different policy and practice settings demonstrates contrasting expressions and experiences of how men contribute to ECEC. This article presents findings from a study in Edinburgh, Scotland and Tianjin, China. The study explored how male and female practitioners and children talk about gender and how gendered relationships and roles are 'performed' in practice settings. In the two contexts, national/regional policy aims to raise the number of men working in ECEC, but in both cases and in different ways the inclusion of men in ECEC reinforces cultural gender norms as much as interrupting them. This research points to the need for comparative research to include observation data and practitioners' and children's views to enhance understanding of how global discourses of ECEC are enacted in different contexts.